(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to observe the effects of Ligustrum lucidum polysaccharide on immune functions of hydrocortisone-induced immuno-suppressed mouse model. There were phagocytic function of mouse perito-neal macrophage, condition of formation of hemolysin and hemolytic plague as well as condition of mouse lymphocyte transformation. The results indicate that through comparison between high-dose, medium-dose, low-dose L. lucidum polysaccharide groups, lentinan group and model group, phagocytic rate and phagocytic index of peritoneal macrophage obviously improved, thus obviously enhancing formation of hemolysin and hemolytic plague, and obviously improving the transformation rate of peripheral blood lymphocyte. Therefore, L. lucidum polysaccharide could markedly improve the immune functions of hydrocortisone-induced immunosuppressed model mouse.